Diabetic neuropathy and oxidative stress: a systematic review focused on oxidative stress biomarkers analysis - Cunha, Sofia (2018)
Diabetic neuropathy is a worldwide disease with great impact in modern society. Diabetes may lead to the overproduction of reactive oxygen species, resulting in an imbalance in body’s redox homeostasis. Oxidative stress is pointed as an important phenomenon associated with several disease states, including diabetic neuropathy.